Comparison of THP-1 Macrophages Viability in Different Types of Culture Vessel: Comparison of Thp-1 Macrophages Viability in Different Types of Culture Vessel - Zahidah Nasuha Mohd Yasin; Fatin Najiah Mohd Idrus; Get Bee Yvonne-Tee (Journal of Tropical Life Science, 2023)
The ox-LDL generated apoptotic bodies using THP-1 macrophage is a useful tool to study foam cell formation in atherosclerosis. However, the common problem is the cells in the negative control (i.e., absence of ox-LDL) undergo apoptosis. Therefore, the type of cell culture vessel was proposed to be the key factor contributing to cell apoptosis. The THP-1 cells were differentiated into M1 macrophages using 10 ng/μL PMA, 5 ng/μL LPS, and 20 ng/μL IFN-? while 5 ng/μL PMA, 20 ng/μL IL-4 and 20 ng/μL IL-13 were used to differentiate THP-1 into M2 macrophages. Two types of cell culture vessels (6-well plate and T25 flask) were used to culture the macrophages. The cells were subsequently stained using Annexin V-FITC and Propidium Iodide prior to flow cytometry analysis. Interestingly, both M1 and M2 macrophages cultured in the T25 flask resulted in a significantly higher percentage of cell viability compared to macrophages cultured in 6-well plate [M1: 84.15% ± 4.39 vs 8.02% ± 1.55, p < 0.0001; M2: 95.95% ± 1.74 vs 10.50% ± 0.05, p < 0.0001]. In summary, the type of culture vessel is a vital factor in determining cell viability attributed to the surface area and cell seeding density in different types of vessels. Keywords: Apoptosis, cell viability, culture vessel, macrophage, THP-1